ANALYSIS OF STUDENTS' MATHEMATICAL POWER IN TERMS OF STIFIN TEST - Isna Rafianti; Heni Pujiastuti (IKIP Siliwangi and I-MES, 2017)
This research is motivated by the poor performance of students in particular mathematical power. One reason is that learning tends to be centered on teachers who emphasize the procedural process, mechanistic task and less provide opportunities for students to develop the ability to think mathematically. In terms of learning, each individual has their advantages and disadvantages to absorb the lessons given. But in the world of education is now known various methods in order to meet the demands of individual differences, one of which is STIFIn to determine the dominance of machine intelligence to make students more comfortable in the learning process that is expected to enhance the mathematical power. This research approach is qualitative descriptive that seeks to analyze the characteristics of students’ mathematical power in terms of STIFIn. This research was conducted in SMAN 2 Kota Serang, with research subjects are five students of eleven grade derived from each type STIFIn different categories according to STIFIn. Instruments in this study are mathematical power test and interview. The results showed that mathematical power of Thinking and Sensing type has higher than the other type, followed by the type Feeling, Intuiting and the last is the type of Instinct.